A Comparative Study of Black Box Testing and White Box Testing - Verma, Akanksha; Khatana, Amita; Chaudhary, Sarika (International Journal of Computer Sciences and Engineering, 2025)
The most important and time consuming part of software development life cycle is Software testing. Its main purpose is to detect software faults and failures so that defects can be recovered and corrected in early phases of testing. Software Testing is a process of confirming that the product software that has been manufactured by programmers is a good quality product and also to assure that the product is working according to the specification that has been intended so that customer satisfaction can also be possible. In this paper, we have described and compared the two most important and commonly used software testing techniques for detecting errors, which are: Black Box Testing and White Box Testing.